2017
DOI: 10.1186/s12879-017-2242-y
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of chronic hepatitis C in immigrants and non-immigrants in Quebec, Canada

Abstract: BackgroundImmigrants originating from intermediate and high HCV prevalence countries may be at increased risk of exposure to hepatitis C infection (HCV) in their countries of origin, however they are not routinely screened after arrival in most low HCV prevalence host countries. We aimed to describe the epidemiology of HCV in immigrants compared to the Canadian born population.MethodsUsing the reportable infectious disease database linked to the landed immigration database and several provincial administrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
5
24
1
Order By: Relevance
“…[33][34][35] Mortality rates were generally lower among immigrants than among long-term residents, consistent with the "healthy immigrant effect," whereby new immigrants are typically healthier than those native to a country, 36 including in Canada. 37,38 Greenaway and colleagues 39 found that immigrants in Quebec had lower rates of problematic drug use than nonimmigrants, which may further explain our finding. Rural residents had a greater risk for all-cause mortality, which confirms previous research among people with HIV infection.…”
Section: Opensupporting
confidence: 51%
“…[33][34][35] Mortality rates were generally lower among immigrants than among long-term residents, consistent with the "healthy immigrant effect," whereby new immigrants are typically healthier than those native to a country, 36 including in Canada. 37,38 Greenaway and colleagues 39 found that immigrants in Quebec had lower rates of problematic drug use than nonimmigrants, which may further explain our finding. Rural residents had a greater risk for all-cause mortality, which confirms previous research among people with HIV infection.…”
Section: Opensupporting
confidence: 51%
“…This finding is consistent with the previous studies that showed immigrants were diagnosed with their liver disease after almost 10 years following arrival and at more advanced stage. [24][25][26][27][28] This may be due to lack of healthcare access and health information, poor knowledge of the disease and asymptomatic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…More recently an EDbased, nontargeted, opt-out study found an HCV-positive rate of 7.7%, revealing a significant number of infected patients who did not have traditional risk factors [25]. Additionally, our findings may be an underestimate given the high rate of refusal, and especially the significantly higher number of immigrant patients amongst those who refused testing, since rates of HCV infection amongst immigrants from endemic countries is estimated to be up to 1.7 times higher than non-immigrants [26].…”
Section: Discussionmentioning
confidence: 57%